Case Report: Bilateral globus pallidum internus DBS for treating tremor and dystonia in spinocerebellar ataxia 17: a thirteen-year follow-up - Aparna Wagle Shukla; Shilpa Chitnis; Irene A. Malaty; Pam Zeilman (Dystonia, 2023)
Background: Spinocerebellar ataxia 17 (SCA17) is a rare autosomal dominant trinucleotide disorder. There are no effective therapies for addressing the clinical symptoms of SCA17.Case report: We describe a 46-year-old male who presented with symptoms of generalized dystonia and focal arm tremors manifesting during adolescence. He underwent bilateral globus pallidus (GPi) DBS surgery that led to notable improvements in dystonia and tremor symptoms, impacting his quality of life. At the time of surgery, he did not show cerebellar ataxia features; however, these began to manifest 2 years after DBS surgery. He subsequently underwent genetic testing that confirmed the SCA17 diagnosis. Currently, at 13 years of follow-up, although the ataxia has continued to worsen, DBS therapy has led to persistent improvements in dystonia, tremor, and many aspects of quality of life.Discussion: The current case indicates that DBS is a promising symptomatic therapy for dystonia and tremor in SCA17.